A demographic and clinical panorama of a sixteen-year cohort of soft tissue sarcoma patients in Brazil - Luiza Ohasi de Figueiredo; Augusto Afonso Guerra Júnior; Francisco de Assis Acurcio; Alessandra Maciel Almeida; Mariângela Leal Cherchiglia; Alberto Julius Alves Wainstein; Luiz Claudio Santos Thuler; Angélica Nogueira-Rodrigues (Scientific Reports, 2021)
Abstract Little is known about soft tissue sarcomas (STS) in Brazil, once the federal statistics regarding estimates on incidence and mortality of the most common cancers that affect the Brazilian population currently do not include STS. This study aims to perform a broad evaluation and description of the epidemiological profile, access to treatment and main clinical outcomes of the Brazilian STS patient. A population-based cohort study of 66,825 patients who underwent procedures related to STS treatment registered in the Brazilian public health system (Sistema Único de Saúde, SUS) databases. Median age was 57 years, 30% of them older than 65 years and 50.7% of the cohort was female. The majority, 50,383 patients (75.4%), was diagnosed between 2008 and 2015. Most prevalent anatomic sites were upper and lower limbs (12.6%) and the registry of sarcomas without a specific location comprehended 29.7% of the cohort. The majority of patients resided in the Northeast (40.2% of the patients). Surgery was the first treatment modality in 77.7% of the cases. For survival analysis, only patients with stage and histological grade information were included. The 1-, 5- and 10-year survival rate of the patients was, respectively, 75.4% (95% CI = 74.1–76.7%), 43.4% (95% CI = 41.5–45.5%) and 18.6% (95% CI = 14.8–23.3%).